2012
DOI: 10.1088/0960-1317/22/7/075001
|View full text |Cite
|
Sign up to set email alerts
|

A level set methodology for predicting the effect of mask wear on surface evolution of features in abrasive jet micro-machining

Abstract: A previous implementation of narrow-band level set methodology developed by the authors was extended to allow for the modelling of mask erosive wear in abrasive jet micro-machining (AJM). The model permits the prediction of the surface evolution of both the mask and the target simultaneously, by representing them as a hybrid and continuous mask-target surface. The model also accounts for the change in abrasive mass flux incident to both the target surface and, for the first time, the eroding mask edge, that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
(171 reference statements)
0
7
0
Order By: Relevance
“…For example, Wensink et al [29] used electroplated copper masks with AJM in order to create channels as small as 50 μm wide on glass, and observed them to be highly erosion resistant. Ghobeity et al [31] and Burzynski et al [32] used steel shims to machine and model the surface evolution of AJM features in glass and PMMA with aspect ratios (depth to width) greater than one.…”
Section: Mask Materials Used In Abrasive Jet Micro-machiningmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Wensink et al [29] used electroplated copper masks with AJM in order to create channels as small as 50 μm wide on glass, and observed them to be highly erosion resistant. Ghobeity et al [31] and Burzynski et al [32] used steel shims to machine and model the surface evolution of AJM features in glass and PMMA with aspect ratios (depth to width) greater than one.…”
Section: Mask Materials Used In Abrasive Jet Micro-machiningmentioning
confidence: 99%
“…Despite these advantages, they were found to not be suitable for making high aspect ratio features, since they are relatively thin, erode quickly, and can deform elastically [34]. Burzynski et al [32] modeled the effect of their wear on the surface evolution of features made using AJM, reported that the mask wear resulted in undesirable widening of the machined feature profiles in both brittle targets and ductile targets. In Chapter 6, elastomeric masks are used in a novel rotating mask configuration that extends their lifetime, whilst also increasing their flexibility to create a wider variety of features.…”
Section: Mask Materials Used In Abrasive Jet Micro-machiningmentioning
confidence: 99%
See 2 more Smart Citations
“…The predicted channel and eroded mask shapes were directly compared against measurements on channels machined in both glass and PMMA targets, using two different masks, thus verifying the predictive capability of the methodology. The majority of the material in this chapter has been submitted for publication and is currently under review [50].…”
Section: Motivationmentioning
confidence: 99%